Designing an Organizational Culture Model Based on Lean Leadership (Case Study: Islamic Azad University) - Nadri, Khadijeh; Imani, Mohammad Naghi; Nazem, Fattah (Management Strategies and Engineering Sciences, 2024)
Organizational culture primarily reflects the leaders of an organization. Leaders influence culture through their strategies, practices, values, and leadership styles. Lean leadership in higher education, which contributes to reducing costs and waste while improving quality and effectiveness in universities, has gained significant attention. This study aimed to design an organizational culture model based on lean leadership at the Islamic Azad University. Data were collected through semi-structured interviews with faculty members and department managers of the Islamic Azad University in Tehran. By analyzing the interview content and extracting codes, dimensions, and components of the organizational culture model based on lean leadership were identified and developed. The triple coding process—open, axial, and selective—was conducted using MAXQDA software (version 2020). The findings revealed that 96 concepts were labeled during the open coding process. These initial concepts were reviewed, analyzed, and categorized to identify the components. As a result, 19 components were extracted during the axial coding stage from the initial 96 open codes. Finally, nine main dimensions were identified during the selective coding stage. The classification of results focused on designing a model consisting of nine dimensions: customer focus, continuous improvement, employee participation, academic stakeholders, aligning lean thinking with higher education, inclusive and supportive lean university structures, strategic university planning based on lean principles, a systemic approach to university administration, and long-term managerial thinking.